(untitled) (Revista Contexto & Educação, 2024)
The text intends to understand, from the perspective of the relationship between philosophy of education, psychoanalysis and education, the feasibility of institutionalizing informed dialogical practices as a counterpoint and prevention of violence in education. For this, it deals with the difficulties of their records in archives and the imperative of (re)building dialogued and propositional mediations, with a view to their better understanding and coping in the coexistence of the student and educator relationship. The aim is to hermeneutically investigate the contributions of Freud, Adorno and Derrida on the relationship between violence, language and memory. Also, want to listen to teachers and managers of public schools in five (5) municipalities in Rio Grande do Sul, through the analysis of a teaching and research experience carried out through the undergraduate course on Religion Sciences – UAB/UFSM. We aim to deal in an edifying way with the vacant place of teaching in a dialogued and enlightened way, in order to (re)build theoretical mediations and intervention strategies as a way of confronting violence in/in education. In this sense, it raises subsidies subsidies in the dialogic reflection of the pedagogical practice of educators from the educational networks, in order to problematize the meaning of the theory and practice relationship in teacher education, in times of normalizing exception and the absence of files containing specific information from each school.